A Model Suburb for Model Suburbanites: Order, Control, and Expertise in Thorncrest Village - Vitale, Patrick (Urban History Review / Revue d'histoire urbaine, 2011)
In 1945, Marshall Foss began construction of Thorncrest Village, a subdivision in Etobicoke just to the west of Toronto. Foss and urban planner Eugene Faludi envisioned Thorncrest Village as nothing less than a model suburb for postwar Canada. They created a community that embodied the ideals of modern suburban planning: conformity, community, privacy, stability, and a careful mixture of nature and city. They developed an orderly and controlled suburb that secured upper-middle-class residents’ financial investments and their social status. These residents, in turn, placed unbounded faith in Foss and Faludi’s expertise and identified with the Village as a landmark experiment in modern suburban living. Thorncrest Village became a key site that intertwined the expertise of modern urban planning and the identities of elite suburbanites. The values that developers and residents put into place in Thorncrest Village—particularly the pursuit of order and control—are significant components of suburbanization in Canada and elsewhere.